2019
DOI: 10.1108/caer-09-2018-0194
|View full text |Cite
|
Sign up to set email alerts
|

Academic achievement and mental health of left-behind children in rural China

Abstract: Purpose China’s rapid pace of urbanization has resulted in millions of rural residents migrating from rural areas to urban areas for better job opportunities. Due to economic pressures and the nature of China’s demographic policies, many of these migrants have been forced to leave their children with relatives – typically paternal grandparents – at home in the countryside. Thus, while income for most migrant families has risen, a major unintended consequence of this labor movement has been the emergence of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…The second to fifth large groups were those coming from Henan, Guizhou, Anhui, and Sichuan, with the numbers of 667, 574, 509, and 425, respectively. Most existing literature only considered the left-behind children in rural areas [ 33 , 34 , 35 , 36 ], but the left-behind also exist in cities for parents who are away on business trips, or work or study in other cities or countries. Therefore, in the present study, the students coming from cities were taken into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…The second to fifth large groups were those coming from Henan, Guizhou, Anhui, and Sichuan, with the numbers of 667, 574, 509, and 425, respectively. Most existing literature only considered the left-behind children in rural areas [ 33 , 34 , 35 , 36 ], but the left-behind also exist in cities for parents who are away on business trips, or work or study in other cities or countries. Therefore, in the present study, the students coming from cities were taken into consideration.…”
Section: Methodsmentioning
confidence: 99%
“…Our finding that there was no significant difference between the prevalence of mental health problems among left-behind children and non-left-behind children contradicts the majority of existing studies conducted in rural China, which generally show left-behind children to be a disadvantaged subgroup in terms of psychological well-being [ 15 , 63 , 64 , 65 ], though there is another cross-sectional study that also found no differences [ 57 ] and a longitudinal study that found null impacts of parental migration on child mental health [ 32 ]. Mixed results on the effects of parental migration have also been identified in contexts outside of China.…”
Section: Discussionmentioning
confidence: 97%
“…Bully victims are especially vulnerable to mental health issues [ 27 ]. Fourth, rural students in China perform significantly worse than their urban peers in school [ 28 , 29 , 30 , 31 , 32 ]. Feelings of academic incompetence or failure to succeed were shown to increase internalizing symptoms among children [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhao et al (2017) showed that housing expenditure, and thus household welfare, is increased by Rural Dibao participation. In contrast, Han et al (2016) and Wang et al (2019a, b) found that housing expenditure does not increase. The contradictions that exist among these studies make it difficult to describe Rural Dibao's ultimate effect on household welfare.…”
Section: Introductionmentioning
confidence: 88%
“…Han et al (2016) support this argument by showing that participation leads to less expenditure on social activities. Nevertheless, Han et al (2016) as well as Zhao et al (2017) and Wang et al (2019a, b) find some positive impacts of Rural Dibao on rural household welfare (e.g., participation is related to increased health expenditure).…”
Section: Introductionmentioning
confidence: 96%